The Effect of Service Quality, Banking Digitalization, and Customer Relationship Management (CRM) on Customer Loyalty - Panji Anugrah Sampurna; Titis Miranti (Universitas Proklamasi 45, 2022)
Customer loyalty is an essential part of the sustainability of the banking system. Every bank has to maintain that value in some way. However, changes in banking activity due to the COVID-19 pandemic are considered to have an impact on customer loyalty. This also happened at Bank Syariah Indonesia KC Soetta Malang. Banking activities originally carried out conventionally (offline) have changed to online. BSI KC Malang Soetta increased its income every year and experienced a decrease in total expenses. It means that Islamic banking has good development and many enthusiasts. This study aims to look at the factors that maintain customer loyalty at BSI KC Malang by considering the value of service quality, banking digitalization, and customer relationship management (CRM). The study involved 140 customers by adopting a purposive sampling technique. Data retrieval is taken by questionnaire. The data analysis method used Structural Equation Modeling (SEM) with the help of SMART-PLS software. The results show that service quality, banking digitalization, and customer relationship management significantly affect customer loyalty.